2015
DOI: 10.1094/pdis-03-15-0299-fe
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Wilt of Dry-Edible Beans in the Central High Plains of the U.S.: Past, Present, and Future

Abstract: Bacterial wilt, caused by Curtobacterium flaccumfaciens pv. flaccumfaciens, was first recognized and described as a new dry bean disease near Redfield, SD after the 1921 growing season on the farm of the Office of Forage Investigations. Between the late 1930s and the early 1950s it became one of the more problematic bacterial diseases of dry beans. It became an endemic problem in dry bean production throughout western Nebraska and other areas of the central high plains during the 1960s and early 1970s. By the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 20 publications
2
59
0
Order By: Relevance
“…While the results of Harveson et al . () and those of the present study support the hypothesis of latent survival of the bacterial wilt pathogen on a number of nonhost plants, further studies are needed to precisely determine the role of nonhost plants in the survival and spread of this pathogen.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…While the results of Harveson et al . () and those of the present study support the hypothesis of latent survival of the bacterial wilt pathogen on a number of nonhost plants, further studies are needed to precisely determine the role of nonhost plants in the survival and spread of this pathogen.…”
Section: Discussionsupporting
confidence: 71%
“…The results of this study are in agreement with those of Harveson et al . (), that C. flaccumfaciens can survive on a striking number of nonhost plant species including alfalfa, maize, eggplant, pepper, sunflower, tomato and wheat under field conditions. All pathogenic strains of C. flaccumfaciens tested in this study were isolated from solanaceous vegetables grown across the areas where bacterial wilt disease of dry beans, caused by Cff, is widespread (Osdaghi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…b), suggesting that infection with Curtobacterium flacumfaciens , a seed‐borne phytopathogen that is commonly found in beans in Brazil had occurred (Harveson et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…flaccumfaciens (Harveson et al, 2015), when it was found that storms and hail events that caused physical damage to bean plants enhanced the disease, by favoring stomatal opening or bypassing plant defense by creating wounds as entry sites. The effect of rainfall on populations of P. syringae pv.…”
Section: Resultsmentioning
confidence: 99%